2016
DOI: 10.1155/2016/5957404
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Level of mRNA, Protein, and DNA Methylation Status of FOSL2 of Uyghur in XinJiang in Type 2 Diabetes

Abstract: Objective. We investigated the expression levels of both FOSL2 mRNA and protein as well as evaluating DNA methylation in the blood of type 2 diabetes mellitus (T2DM) Uyghur patients from Xinjiang. This study also evaluated whether FOSL2 gene expression had demonstrated any associations with clinical and biochemical indicators of T2DM. Methods. One hundred Uyghur subjects where divided into two groups, T2DM and nonimpaired glucose tolerance (NGT) groups. DNA methylation of FOSL2 was also analyzed by MassARRAY S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Several other genes, including CIDEP , FABP3 , FFAR , CCL2 and PRKCZ , have previously been identified to be differentially methylated in PBLs from diabetic patients[ 48 51 ] and could thus be of potential in the identification of metabolic diseases. Associations between altered levels of DNA methylation and gene expression were observed in T2D patients in several tissues, including PBL[ 13 , 16 , 51 , 52 ], which further supports the potential role of DNA methylation in metabolic diseases.…”
Section: Discussionmentioning
confidence: 63%
“…Several other genes, including CIDEP , FABP3 , FFAR , CCL2 and PRKCZ , have previously been identified to be differentially methylated in PBLs from diabetic patients[ 48 51 ] and could thus be of potential in the identification of metabolic diseases. Associations between altered levels of DNA methylation and gene expression were observed in T2D patients in several tissues, including PBL[ 13 , 16 , 51 , 52 ], which further supports the potential role of DNA methylation in metabolic diseases.…”
Section: Discussionmentioning
confidence: 63%
“…FOS TFs have been implicated in diabetes and glucose homeostasis. Computational analysis has suggested that FOS plays a role in the pathogenesis of T2D (77), and FOSL2 in T2D individuals has been shown to be hypermethylated, leading to lower mRNA and protein expression levels (78). Finally, we observed that TFs FOXA1, TFAP2A and 2C, and GATA3, which are known to be associated with type 2 diabetes risk (79), development, and subsequent maintenance of β cells (80) and insulin secretion (81), were absent in SLC26A9-expressing pancreatic cells in our study and in 2 of the 4 published studies (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that Fosl2 expression plays a role in the positive regulation of insulin and glucose metabolism [ 29 ]. A detailed investigation into the blood DNA methylation status and expression level of the FOSL2 gene found that eight CpG units within the FOSL2 gene had higher methylation rates in T2DM patients, resulting in a significant reduction in FOSL2 mRNA and protein levels compared with normal glucose tolerance (NGT) group [ 31 ].…”
Section: Single or Multiple Gene Studiesmentioning
confidence: 99%